Preeclampsia And Normotensive Pregnant Females Material Serum Endoglin Evalution Dr Vinay V Raman, Post Graduate Cum Tutor, Department Of Biochemistry, BMC&RI (Journal of Pharmaceutical Negative Results, 2023)
An unbalance of angiogenesis, including soluble endoglin, exists that causes preeclampsia. Preeclampsia patients had considerably higher serum soluble endoglin levels compared to women who were not experiencing any complications during their pregnancies.Comparing the serum concentrations of soluble endoglin between pregnant women experiencing preeclampsia and those who had normal blood pressure. Forty pregnant women who were at least 20 weeks along were split evenly into two groups: those with preeclampsia and those without. Venipuncture was used to collect 5ml of blood into a test tube without the use of anticoagulant. Kits were used to perform a one-step sandwich enzyme immunoassay on plasma endoglin with monoclonal antibodies specific to human endoglin. The blood soluble endoglin level was significantly greater in the preeclampsia group (18.52 9.54 vs. 2.2 1.4, p= 0.000), and there was positive association between an elevated serum endoglin level and the probability of pre-eclampsia (r=0.523, P=0.016). The optimal sensitivity and specificity was found at the former was greater whereas the latter was lower than the threshold value of 6.26500 ng/ml.The diagnostic accuracy of serum soluble endoglin for preeclampsia is exceptional.